The Role of Involvement as a Moderating Variable in a Country of Origin Study - Rindang Matoati; Suci Paramitasari Syahlani (Gadjah Mada International Journal of Business, 2017)
The aim of this study is to examine the effect that the country of design and the country of manufacture has on the perceived quality of a product, and the role of involvement as a moderating variable. The conceptual framework has been tested using laboratory experiments that included a 2x2x2 between the subject’s factorial designs. Data have been collected using a randomization method to reduce any bias in the group’s variations. This data were analyzed using a one-way and two-way ANOVA. The results indicate that there is no difference between the high and low points of a product’s perceived quality, based on its country of design. Conversely, a favorable country of manufacture results in a higher perceived quality for its products, than for those of a lower scoring country of manufacture. Furthermore, consumers’ involvement, as a moderating variable, limits the strength of the country of design and the perceived quality’s relationship as this relationship is found to be stronger in circumstances where the consumers’ involvement is greater than in the less involved group’s condition. However, consumers’ involvement does not have any role as a moderating variable in the relationship between the country of manufacture and the perceived quality.